BEHAVIOURAL TARGETING, PERCEPTION OF INTERNET USERS AND CLICK-THROUGH INTENTIONS: IMPLICATIONS FOR DIGITAL ENTREPRENEURS IN NIGERIA - Oladele, Seun; Adigun, Oluwatimileyin; Johnson, Laosebikan S.; Oladele, Femi; Ajani, John (International Journal of Marketing Research Innovation, 2022)
This study assessed the effect of adverts (Ads) based on users’ interest, Ads intrusiveness on the perception of behavioural targeting and click-through intention. The study further examined how the perception of behavioural targeting mediates the interaction between Ads based on users’ interest, Ads intrusiveness and click-through intentions. The study was a descriptive survey, and the approach was deductive. The study collected primary data from a sample of 376 internet users in Nigeria using a cloud-based questionnaire. The data obtained were analysed using descriptive and inferential statistical tools. Partial least square structural equation modelling (PLS-SEM) was used to test the hypotheses. Findings showed that Ads based on users’ interest and Ads intrusiveness predict click-through intentions and the perception of behavioural targeting. Perception of behavioural targeting mediated the interaction between Ads based on users’ interests and click-through intentions. Overall, the study concluded that Ads based on users’ interest and Ads intrusiveness influences the perception of behavioural targeting, which affects click-through intention. Hence the study recommended that digital entrepreneurs carefully design, manage and control the Ads contents they direct to customers. Digital entrepreneurs should exercise caution in implementing their behavioural targeting strategy so as not to breach an acceptable threshold. JEL Classification Codes: M13, M31, M37.